2017
DOI: 10.1097/htr.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Genotypes and Parenting Influence on Long-Term Executive Functioning After Moderate to Severe Early Childhood Traumatic Brain Injury: An Exploratory Study

Abstract: Objective To examine Catechol-O-methyltransferase (COMT) rs4680 genotypes as moderators of the effects of parenting style on post injury changes in parent behavior ratings of executive dysfunction following moderate to severe early childhood traumatic brain injury (TBI). Setting Research was conducted in an outpatient setting. Participants Participants included children admitted to hospital with moderate to severe TBI (n = 55) or orthopedic injuries (OI; n = 70) between ages 3–7 years. Design Prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…These findings add to the growing literature on genetic influences on recovery following pediatric TBI. Recent studies have found associations of the COMT genotype with long-term EF after TBI and OI 20 and of other dopamine-related genes with neurobehavioral recovery after early TBI, including ANKK1. 27 This study expands upon the limited literature by including the interaction of environment and genetic variation on outcomes of pediatric TBI.…”
Section: Fig 1 Behavior Rating Inventory Of Executive Function (Brimentioning
confidence: 99%
See 1 more Smart Citation
“…These findings add to the growing literature on genetic influences on recovery following pediatric TBI. Recent studies have found associations of the COMT genotype with long-term EF after TBI and OI 20 and of other dopamine-related genes with neurobehavioral recovery after early TBI, including ANKK1. 27 This study expands upon the limited literature by including the interaction of environment and genetic variation on outcomes of pediatric TBI.…”
Section: Fig 1 Behavior Rating Inventory Of Executive Function (Brimentioning
confidence: 99%
“…A growing body of evidence suggests that an individual's genetic makeup may also affect recovery. While most current pediatric research on genetics in TBI has focused on the apolipoprotein E (ApoE) gene 5,18,19 and catechol-O-methyltransferase (COMT), 20 research from the adult literature suggests that genes related to preinjury cognitive capacity and reserve also may be associated with EF following TBI. 21 Much of the current research has focused on genes involved in the dopaminergic and serotonergic pathways, which are pathways often implicated in post-TBI cognitive and social impairments.…”
Section: Introductionmentioning
confidence: 99%
“…That is, linking gene profiles of biologic processes associated with recovery with specific gene expression and proteomic factors over time after injury (acute to chronic) would assist in characterizing when these biologic processes are most critical for recovery. For example, inflammatory processes may be critical acutely and chronically after injury (Dalla Libera et al, 2011; White et al, 2013; Juengst et al, 2015; Kumar et al, 2015; Witcher et al, 2015; McKee and Lukens, 2016; Lagraoui et al, 2017), whereas neurotransmitters and behavioral signaling may be more important primarily later after injury (McAllister, 2009; Willmott et al, 2013; Failla et al, 2015; Myrga et al, 2015, 2016; Kurowski et al, 2017a,b; Treble-Barna et al, 2017c). Characterizing these processes would be an important step toward determining when specific treatments may have the greatest impact on recovery and could also severe as a biomarker to provide a more proximal measure of treatment benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to move toward a true precision medicine approach, an improved understanding how genetic and other biologic factors interact with other host, injury-related, treatment, and environmental factors to influence recovery will be critical. Age at injury, sex, and environmental factors, such as parenting style, may interact with genetic factors to influence recovery (Treble-Barna et al, 2016; Kurowski et al, 2017b; Smith-Paine et al, 2018). Prior work by our group demonstrated that, in an adverse parenting environment, a catechol-o-methyltransferase (COMT) polymorphism is protective in regards to neurocognitive functioning 18 months after pediatric TBI (Kurowski et al, 2017b) Integrating genetics, biologic, psychosocial, environmental, and individual factors into analyses to inform development of a comprehensive biopsychosocial model of recovery would allow for better development of individualized prognosis and treatment plans, but requires large-scale, collaborative, multicenter studies (Cotter et al, 2017; Kenzie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation